Descrição histológica, cultivo in vitro de fibroblastos e criopreservação da pele do pavilhão auricular de onça-pintada, panthera onca (linnaeus, 1758) - Praxedes, Érika Almeida (Universidade Federal Rural do Semi-Árido, 2019)
The jaguar is a carnivore of high ecological importance for the world's biodiversity. Its current condition of vulnerability to extinction requires conservation strategies, such as cryopreservation of somatic tissues. Nevertheless, the use of cryopreservation techniques depends on the knowledge of the histological and cellular characteristics of the tissues under study. Therefore, the aims were described by histological techniques and by in vitro culture the apical ear skin (Step 1) and to compare three cryopreservation techniques [slow freezing (SF), direct vitrification in cryotubes (DVC) and solid-surface vitrification (SSV)] on the conservation of these jaguar samples (Step 2). Thus, fragments were recovered derived from five animals from zoos of Brazil. In the first step, samples of only two animals, one with yellow and one black pelage, were evaluated for skin thickness, cell quantification and distribution, percentage of collagen matrix, proliferative activity and tissue viability after culture. For the second step, fragments were cryopreserved by SF, DVC or SSV, and compared to non-cryopreserved fragments (control) for skin thickness, number of cells, percentage of collagen matrix, and tissue proliferative activity. Moreover, cells resulting from the cultured fragments were evaluated for morphology, adhesion, confluence, viability, proliferative and metabolic activity. Thus, in the first stage, the histomorphometric study showed a total skin thickness of 273.2 μm and 274.6 μm for jaguars of yellow and black pelage, respectively. Likewise, melanocytes and fibroblasts for yellow jaguar were 9.3 e 23.0 and to black jaguar were of 11.3 e 26.8, respectively. A percentage of collagen matrix of 67.0% e 49.0% was observed for jaguars of yellow and black pelage, respectively. Additionally, both animals had a cell proliferative activity ranging from 1.20–1.30 and all the fragments were able to promote cell detachment, reaching the subconfluence between 10 and 15 days. In the second step, all the cryopreserved fragments, regardless of the technique employed, showed a reduction in the thickness of the dermis and skin (P < 0.05). Although a collagen matrix similar to the control group was observed only for the fragments derived from the SF and SSV groups, all techniques maintained the number of fibroblasts (P > 0.05). Additionally, DVC and SSV maintained tissue proliferative activity after warming. After culture, only SF and SSV were efficient for the recovery of somatic cells, according to most of the evaluated parameters. In conclusion, the apical ear skin of the yellow and black jaguar has some variations relative to other mammals, regarding thickness, collagen matrix density, and number of melanocytes and fibroblasts. Nevertheless, the pattern of cell growth was similar to other wild felids. Moreover, SSV was the most efficient technique for jaguar skin cryopreservation when compared to DVC and SF. These results will contribute to the formation of crybanks of this species, directing the adequate cryopreservation of somatic samples for applications in regenerative medicine and assisted reproduction technologies
Keywords: Bancos de recursos biológicos; Criopreservação tecidual; Células somáticas; Biological resources banks; Tissue cryopreservation; Somatic cells; CIENCIAS AGRARIAS::MEDICINA VETERINARIA